FORMULASI DAN EVALUASI FISIK SEDIAAN LIP BALM EKSTRAK ETANOL UMBI BIT (Beta vulgaris var. rubra (L) Moq.) SEBAGAI PEWARNA ALAMI - Isnaini, Erlin Devi; Suhesti, Iin; Dewi, Aptika Oktaviana Trisna (Jurnal Farmasindo: Jurnal Penelitian dan Pengabdian Masyarakat, 2020)
Beetroot (Beta vulgaris var. rubra (L) Moq.) has the pigment betasianin which produces a red color and is often used as a natural coloring agent in food so that it can be developed to be used as a dye in cosmetic products. The purpose of this study was to determine the lip balm preparation formulation of beetroot extract (Beta vulgaris var. rubra (L) Moq.) as a natural dye and physical evaluation. In this study using a descriptive experimental method using variations in the concentration of beetroot extract. The variations in the concetration of beetroot extract were F1 0%, F2 1%, F3 5% and F4 10%. From each formula, a physical lip balm test was carried out including the organoleptic test, homogeneity test, pH test, melting point test, and preference test. The result showed that the lip balm preparation on F1 was yellow, F2 was peach, F3 was pink and F4 was maroon. F1, F2, F3 have the distinctive smell of oleum cacao, while F4 has the distinctive smell of lanolin. And semi solid preparation. Homogeneity test F1, F2, F3 and F4 have homogeneous preparations. pH test at F1 5.26; F2 5.03; F3 4.87 and F4 4.76. melting point test of all formulas melting at 50°C for F1 and F2 for 12 minutes, F3 10 minutes and F4 for 6 minutes. The preference test concluded that the panelists preferred F4.